To achieve a sustainable blue future, progress assessments must include interdependencies between the Sustainable Development Goals - Nash, KL; Blythe, JL; Cvitanovic, C; Fulton, EA; Halpern, BS; Milner-Gulland, EJ; Addison, PFE; Pecl, GT; Watson, RA; Blanchard, JL (Cell Press, 2020)
The Sustainable Development Goals (SDGs) were designed to address interactions between the economy, society, and the biosphere. However, indicators used for assessing progress toward the goals do not account for these interactions. To understand the potential implications of this compartmentalized assessment framework, we explore progress evaluations toward SDG 14 (Life below Water) and intersecting social goals presented in submissions to the UN High-Level Political Forum. We show that there is a disconnect between the apparent progress shown by indicators and long-term sustainability; for example, short-term gains in reducing hunger or poverty might be undermined by poor ocean health, particularly in countries dependent on fisheries or developing their blue economy. We suggest an extension to existing indicator assessments to integrate scenarios and social-ecological modeling. This approach would ensure that decision makers are provided with knowledge fundamental to directing actions to attain SDGs while minimizing unintended outcomes due to interactions among goals.